(untitled) (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of progressive muscle relaxation on fatigue scores in lung cancer undergoing chemotherapy. This research method is quasi-experimental in the form of a Pre-Test and Post-Test with Control Group Design. The research showed an effect of progressive muscle relaxation on the fatigue score, p-value 0.000 < α 0.005. The dominant factor in fatigue is the frequency of chemotherapy. In conclusion, there is an influence of progressive muscle relaxation on fatigue scores. Keywords: Fatigue, Lung Cancer, Progressive Muscle Relaxation